Interleukin‐38 promotes skin tumorigenesis in an IL‐1Rrp2‐dependent manner. (17th May 2022) - Zhou, Hong; Zhao, Qixiang; Yue, Chengcheng; Yu, Jiadong; Zheng, Huaping; Hu, Jing; Hu, Zhonglan; Zhang, Haozhou; Teng, Xiu; Liu, Xiao; Wei, Xiaoqiong; Zhou, Yuxi; et al.
Abstract: Interleukin‐38 (IL‐38) is strongly associated with chronic inflammatory diseases; however, its role in tumorigenesis is poorly understood. We demonstrated that expression of IL‐38, which exhibits high expression in the skin, is downregulated in human cutaneous squamous cell carcinoma and 7, 12‐dimethylbenzanthracene/12‐O‐tetradecanoyl phorbol‐13‐acetate‐induced mouse skin tumorigenesis. IL‐38 keratinocyte‐specific knockout mice displayed suppressed skin tumor formation and malignant progression. Keratinocyte‐specific deletion of IL‐38 was associated with reduced expression of inflammatory cytokines, leading to reduced myeloid cell infiltration into the local tumor microenvironment. IL‐38 is dispensable for epidermal mutagenesis, but IL‐38 keratinocyte‐specific deletion reduces proliferative gene expression along with epidermal cell proliferation and hyperplasia. Mechanistically, we first demonstrated that IL‐38 activates the c‐Jun N‐terminal kinase (JNK)/activator protein 1 signal transduction pathway to promote the expression of cancer‐related inflammatory cytokines and proliferation and migration of tumor cells in an IL‐1 receptor‐related protein 2 (IL‐1Rrp2)‐dependent manner. Our findings highlight the role of IL‐38 in the regulation of epidermal cell hyperplasia and pro‐tumorigenic microenvironment through IL‐1Rrp2/JNK and suggest IL‐38/IL‐1Rrp2 as a preventive and potential therapeutic target in skin cancer. Synopsis: Decreased inflammation and epidermal cell proliferation in Il‐38 cKO mice suppress skin tumor formation and malignant progression. IL‐1Rrp2/JNK pathway is crucial for IL‐38 mediated expression of inflammatory cytokines and proliferation and migration of tumor cells. Interleukin‐38 (IL‐38) is downregulated in human cutaneous squamous cell carcinoma and DMBA/TPA‐induced mouse skin tumorigenesis. IL‐38 keratinocyte‐specific deletion ameliorates DMBA/TPA‐ induced skin tumors, reduces the number of immune cells and expression of inflammatory cytokines. IL‐38 forms a complex with IL‐1Rrp2 and activates the JNK/AP‐1 signal transduction pathway in an IL‐1Rrp2‐dependent manner. The proliferation and migration of tumor cells and expression of inflammatory cytokines are induced by IL‐38 via IL‐1Rrp2/JNK. Abstract : Decreased inflammation and epidermal cell proliferation in Il‐38 cKO mice suppress skin tumor formation and malignant progression. IL‐1Rrp2/JNK pathway is crucial for IL‐38 mediated expression of inflammatory cytokines and proliferation and migration of tumor cells.